Conversions on the rise - modernizing e-mail marketing practices by utilizing volunteered data - Hartemo Mari (Emerald, 2025)
Purpose
The purpose of the study is to examine how utilizing volunteered data influences the response and unsubscribe rates of e-mail marketing to consumers.
Design/methodology/approach
In three longitudinal field experiments conducted among 1,864 applicants of a higher education institution, the study compares customized marketing e-mails based on volunteered consumer data to e-mails that are personalized based on observed consumer data and to control e-mails that are not tailored by the marketer at all.
Findings
The results indicate that marketers should make consumers active participants in the communication process, as response rates are higher in those e-mails where volunteered data are utilized. However, the unsubscribe rate is the highest in customized e-mails.
Research limitations/implications
The authors demonstrate that e-mails displaying empowering aspects influence consumers' behaviors and lead to outcomes that mostly outperform non-empowered e-mails.
Practical implications
Compared to other forms of interactive marketing, e-mail has lagged behind in both popularity and customer-friendly implementation. However, it has the potential to succeed if marketers pay more attention to consumer empowerment. As over 306 billion e-mails are sent worldwide daily and 75% of marketers use e-mail when contacting customers, the increase in response rates can have a significant influence on their returns.
Originality/value
Unlike prior research the focus was on the process of tailoring, this perspective supports customer advocacy and emphasizes consumers' important role in creating engaging, empowering e-mail marketing communication.